The Development of Islamic Character Building Model (Phenomenological Study In Islamic College Students In Jakarta at Millennial) - Nur Afif (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims to determine the application of Islamic values to students at Islamic universities and to determine the development of a character formation model based on Islamic rules for students at Islamic universities. This research useda qualitative approach with library methods. The research results showed that application of Islamic values to students at Islamic universitieswith characters formulated as reinforcements for Islamic education so that character education is essentially the spirit of Islamic education. The formation of the character of Islamic education basically refers to the sources contained in the life guidelines of Muslims, namely the Al-Qur'an, Al-Sunnah, and Ijtihad. Development of a character formation model based on Islamic rules for students at Islamic universitiesselike the millennial generation, it takes time and process. Therefore, character formation in students requires a conducive attitude and value orientation, these include: attitude, orientation and practice of mutual trust, discipline, working hard, prioritizing education, enforcing the rule of law, as well as our shared identity in a nation.